O passado e o presente da África e Europa - Green, Toby (Afro-Ásia, 2019)
Resenha de: BENNETT, Herman L.. African Kings and Black Slaves: Sovereignty and Dispossession in the Early Modern Atlantic. Filadélfia: University of Pennsylvania Press, 2019. 240p.